The Change in The Activity of The American Intelligence Services in The Security Context of the Last 24 Years - Stefan, Georgescu -; Zidaru, Marian; Dragan, Cristi (Journal of History Culture and Art Research, 2014)
The Change in The Activity of The American Intelligence Services in The Security Context of the Last 24 Years Abstract The security events dynamics poses an overwhelming challenge for the decision makers’political agenda, priorities. The wide range of risks and rhythm of significant security events determine a difficult enterprise for security theories. A scientific analysis of the security evolutions entails a profound historical introspection and an appropriate understanding of the security events with significant impact over the global evolutions. Probably in the next period of time, hundreds of papers will be written regarding the period since 9/11. The aim of this paper is to provide a perspective over the security context, and the intelligence services activity of the last 15 years, period of time dramatically divided by the unprecedented shock and suffering in the history of the from 9/11. The reorganization of the Western Intelligence Community was ordered as a result of the September 11th attacks and with future counterterrorism efforts in mind. Specifically, the 9/11 terrorists exploited the wall between the U.S.’s foreign and domestic intelligence collection efforts, and yet the IRTPA and EO 12333 avoid the issue of how to best integrate foreign and domestic intelligence while minimizing the threat to civil liberties. This manner in which the Western Countries separates its foreign and domestic intelligence collection is particularly exploitable by terrorists and non-state actorsthose currently posing one of the most serious threats to international security. To ensure both the best intelligence integration possible as well as the defense of civil liberties, clear and sensible rules should be formed which dictate how intelligence from these two spheres is collected and in what way and at what level it is integrated and disseminated.